The utilisation of online alternative media and its implications towards participatory democracy: a Malaysian case / Azlina Kamaruddin - Kamaruddin, Azlina (2015)
This study examines the utilisation of online alternative media and its implications towards participatory democracy. Since the enactment of the Communication and Multimedia Act 1999, online alternative media such as Malaysiakini, Malaysia Today, and the Malaysian Insider have played a pivotal role in many political events including the post-Mahathir-Anwar political crisis, the 2008 financial crisis, election campaign, Anwar's sodomy case, and Dr. Hasan Ali's disclosure of PAS weaknesses. Online alternative media assist in spearheading some other relevant issues that reflect the undercurrent of discontentment or otherwise the participation of peoples' voices towards democracy. Dissident voices become aloud without fear to voice out their opinions and dissatisfaction on political issues via online alternative media. Indirectly, it forms a force for a shift of democratic paradigm. Among others this study has explored the role of online alternative media and answered the enquiry of how Malaysians have utilised it for participatory democracy. This study employed the qualitative research method by means of doing semi-structured interviews and qualitative content analysis as data analysis techniques. Within this research approach, examples of the democratic phenomenon were analysed to gain a sense of its general essence. The findings imply that participatory democratic stance via the alternative media is less significant. There were instances where the people voices through online alternative media have gained attention from the policy and decision-makers, and in some other instances it has worked hand in hand with the traditional media.